Bright Nitrogen-Vacancy Centers in Diamond Inverted Nanocones - Jeon, Seong-Woo; Lee, Junghyun; Jung, Hojoong; Han, Sang-Wook; Cho, Young-Wook; Kim, Yong-Su; Lim, Hyang-Tag; Kim, Yanghee; Niethammer, Matthias; Lim, Weon Cheol; Song, Jonghan; Onoda, Shinobu; et al. (AMER CHEMICAL SOC, 2020)
Quantum emitters with long-lived quantum memories are a promising scalable quantum system for repeater-based quantum communications, quantum sensing, and distributed quantum computing networks. Although color centers in solids have been successful, further improvements in the efficiency of optical control and detection and scalability are necessary for practical uses. Here, we demonstrate that single nitrogen-vacancy centers can be efficiently coupled in diamond inverted nanocones that can be fabricated directly on the high-quality CVD diamond surface by the alldirection diagonal dry etching using a solid cone-shaped Faraday cage. Since the inverted cone shape allows efficient photon collection thanks to the single-directional guiding of photons, we report 20-fold enhancement in the photon collection efficiency from a single emitter while preserving a long electron spin coherence time. Furthermore, we show that an inverted nanocone can be picked and placed on the target position with desired orientation by using conventional microprobe tips. The demonstrated structure can also be applied to similar emitters in other solids; thus, it can be used for finding new possibilities for scalable photonic quantum devices.
Keywords: SINGLE-PHOTON SOURCES; QUANTUM EMITTERS; SPIN; ENTANGLEMENT; SPECTROSCOPY; INTEGRATION; PLATFORM; QUBITS; LIGHT